Education for Sustainable Development in Morocco: An Analytical Study in Light of the Indonesian Experience - EL HADRI, Mohamed; AIT AGHZZAF, Ahmed; CHERAI, Bouamama; LAHLALI, Abdelouahed (Universitas Negeri Semarang, 2025)
In recent decades, sustainable development has drawn worldwide attention as economic, social, and environmental challenges grow. Education plays a key role in equipping individuals with the knowledge, values, and skills necessary to achieve the Sustainable Development Goals (SDGs). This study examines the current state of education for sustainable development in Morocco and compares it with Indonesia's recognized successes. We used a mixed-method approach: a systematic literature review focused on three aspects - (1) integrating sustainable development concepts into school curricula, (2) the role of educational institutions in promoting sustainability, and (3) awareness among teachers and students about the SDGs. Findings reveal gaps in the Moroccan education system’s application of sustainable development principles compared to Indonesia, particularly showing Morocco lags behind Indonesia in curriculum content, teacher preparedness, and institutional strategy. The study offers recommendations to improve curricula, raise teacher capacity, and strengthen institutions aiming to create a Moroccan model aligned with international best practices. Education equips people with the knowledge, values, and skills needed to achieve the Sustainable Development Goals (SDGs). This study examines education for sustainable development in Morocco and compares it with Indonesia's recognized successes. We used a mixed-method approach: a systematic literature review focused on three aspects—(1) integrating sustainable development concepts into school curricula, (2) how educational institutions promote sustainability, and (3) awareness among teachers and students about the SDGs. Findings show Morocco lags behind Indonesia in curriculum content, teacher preparedness, and institutional strategy. The study offers recommendations to improve curricula, raise teacher capacity, and strengthen institutions, aiming to create a Moroccan model aligned with international best practices.